WYOBRAŹNIA KARTOGRAFICZNA WOBEC KANONU LITERACKIEGO - Karpowicz, Agnieszka; Madurowicz, Mikołaj (Prace Polonistyczne, 2024)
The aim of the article is to show the importance of cartography and the cartographic imagination in the process of de/re/constructing a literary work and to demonstrate the significance of geographical and cartographic research in historical literary and cultural discourse. The text presents an interdisciplinary dialogue between a cultural/literary scholar and a human geographer/cartographic theorist on the Polish literary canon of the twentieth century in the context of geocriticism as well as cartographic literary studies. What serves as a starting point for thinking about the reconfiguration of the canon from such a cross-disciplinary perspective is an analysis of Leopold Buczkowski’s oeuvre.